Development of TPACK Based-Learning Media Oriented Towards Students' Motivation and Mathematics Outcomes - Dinda Dwi Kartika, Aulia; Kurniawan, Eka (Balai Publikasi Indonesia, 2023)
This study aims to develop Technological Pedagogical Content Knowledge (TPACK)-based learning media oriented towards motivation and mathematics learning outcomes that are valid, practical and effective. The subjects in this study are class VIII students at one of the junior high school in Mataram. This type of this study is Research and Development with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. Data analysis in this study was carried out using descriptive quantitative and qualitative regarding the advisibility of learning media obtained from assessment or validation sheets, analysis of the practicality of learning media obtained from student response questionnaires and teacher responses to learning media, and analysis of the effectiveness of learning media obtained from posttest results. The study results obtained that: TPACK-based learning media has been developed is suitable for use as learning media with high validity; TPACK-based learning media is practically used as learning media with a practicality score of 79.67%; The N-gain value for increasing students matemathics learning motivation is 43.34% in the medium category, while for increasing students matemathics learning outcomes it is 56.74% in the medium category. Based on the results, TPACK-based learning media is suitable for use, practically applied for learning, less effective for increasing learning motivation, and quite effective in improving learning outcomes